2009
DOI: 10.1123/ijsnem.19.2.127
|View full text |Cite
|
Sign up to set email alerts
|

Heart-Rate Response to Sympathetic Nervous Stimulation, Exercise, and Magnesium Concentration in Various Sleep Conditions

Abstract: The aim of this study was to clarify the mechanism of impaired exercise tolerance in chronic sleep-restricted conditions by investigating variables related to heart-rate (HR) response to sympathetic nervous stimulation. Sixteen healthy men (mean age 21.5 years) were tested in a control state, acute sleep-loss state, and chronic sleep-restricted state. Participants underwent cardiopulmonary exercise testing in each state. Their norepinephrine (NE) concentration was measured before and immediately after exercise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 14 publications
(15 reference statements)
1
12
2
Order By: Relevance
“…Otherwise, Jarraya et al (2013) clarified that the adverse effect of the PSDEN could be explained by the absence of paradoxical sleep, which increases at the end of night to involved in the synchronization of the circadian system. On the other hand, the present findings are in disagreement with previous studies which found no modification in endurance intensive performances after SD ( Azboy and Kaygisiz, 2009 ; Chen, 1991 ; Goodman et al, 1989 ; Mejri et al, 2014c ; Mougin et al, 1991 ; Oliver et al, 2009 ; Omiya et al, 2009 ; Racinais et al, 2004 ). These contradictory results could be explain by the differences in fitness level of participants, durations and intensities of the exercise (i.e., continuous exercise, submaximal, or maximal exercise until exhaustion, intermittent exercise), time-of-day of measurements (i.e., morning, afternoon, evening), as well as types and durations of SD (i.e., TSD, PSD in the beginning, the middle, or the end of night).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Otherwise, Jarraya et al (2013) clarified that the adverse effect of the PSDEN could be explained by the absence of paradoxical sleep, which increases at the end of night to involved in the synchronization of the circadian system. On the other hand, the present findings are in disagreement with previous studies which found no modification in endurance intensive performances after SD ( Azboy and Kaygisiz, 2009 ; Chen, 1991 ; Goodman et al, 1989 ; Mejri et al, 2014c ; Mougin et al, 1991 ; Oliver et al, 2009 ; Omiya et al, 2009 ; Racinais et al, 2004 ). These contradictory results could be explain by the differences in fitness level of participants, durations and intensities of the exercise (i.e., continuous exercise, submaximal, or maximal exercise until exhaustion, intermittent exercise), time-of-day of measurements (i.e., morning, afternoon, evening), as well as types and durations of SD (i.e., TSD, PSD in the beginning, the middle, or the end of night).…”
Section: Discussioncontrasting
confidence: 99%
“…The present findings showed that no change was spotted in HR peak and RPE in responses to YYIRT following the two types of PSD. These results are well in agreement with other published investigations which revealed that did not change exercise HR ( Azboy and Kaygisiz, 2009 ; Chen, 1991 ; Goodman et al, 1989 ; Martin and Chen, 1984 ; Martin and Gaddis, 1981 ; Meney et al, 1998 ; Mejri et al, 2014c ; Oliver et al, 2009 ; Omiya et al, 2009 ; Plyley et al, 1987 ; Ricardo et al, 2009 ) and RPE ( Meney et al, 1998 ; Mejri et al, 2014c ; Oliver et al, 2009 ). This last result affirmed the hypothesis that RPE is normally closely related to HR ( Borg, 1971 ).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…In rats, Mg deficiency is associated with an increased amplitude in daily variation of sleep and slow--wave sleep delta power, and has been noted to shorten life span and lower reproductive ability (Chollet et al, 2001;Motta et al, 1998). In humans, chronic sleep deprivation is associated with progressively decreasing levels of intra--cellular Mg, reduced duration of cardio--pulmonary exercise and increased hyper--sensitivity of the chronotropic response to sympathetic nervous stimulation (Omiya et al, 2009). Intriguingly, Mg depletion is associated with decreased melatonin and its supple--mentation alleviates the symptoms (Billyard et al, 2006;Depoortere et al, 1993;.…”
Section: Magnesium Interaction With Stress Pathwaysmentioning
confidence: 99%